Behaviour of FRP strengthened RC Beams with concrete patch repairs subjected to impact loading - Habimana, Philbert (Concrete Materials and Structural Integrity Research Unit (CoMSIRU), 2017)
The acceptable performance levels and serviceability of reinforced concrete (RC) structures are always the priorities of asset managers, engineers and researchers in any country. RC structures in service may fail to adequately perform due to changes in functionality, corrosion attack on the reinforcing bars, lack of proper and timely maintenance, and loading and standards updating, among other reasons. Impact loading is an extreme form of loading that can damage RC structures such as bridges, interchanges and flyovers during their life span. The repair and strengthening of deteriorating RC structures in service, by using concrete patch repairs and fibre reinforced polymers (FRP) respectively, has attracted a lot of attention from researchers and engineers. Nevertheless, these rehabilitated RC structures in service are susceptible to future deterioration with adverse effects. Inspection and periodic maintenance of strategic RC structures in use are essential for their safe serviceability and to avoid or mitigate economic loss. This experimental study was conducted on fifteen RC beams with the size of 155 x 254 x 2000 mm, in order to study their behaviour under impact loading testing. Twelve out of these fifteen RC beams were intentionally damaged by uniformly reducing 14 % of the cross-section of their main reinforcing bars, as this simulated the effects of corrosion on RC structures. The drop test, with the impactor applied from varying drop heights, was selected from the different types of impact loading testing methods and used in this research. Each tested RC beam was subjected to eight consecutive drop tests. During this experimental study 120 tests were performed and, from these tests, dynamic responses were recorded for analysis. Two transducers, a load cell and high-speed camera (HSC), were used to record data. In general the captured and stored dynamic responses led to the extraction of contact forces and deflections results. In addition, the HSC recorded video footage of the impact scenarios of the RC beams. The combined use of software such as Photron FASTCAM Analysis (PFA) and Matlab R2014a enables the acquisition of deflection results and, on the basis of these results, residual deflection